2020
DOI: 10.1021/acs.nanolett.0c00201
|View full text |Cite
|
Sign up to set email alerts
|

Inter-layer-calated Thin Li Metal Electrode with Improved Battery Capacity Retention and Dendrite Suppression

Abstract: An inter-layer-calated thin Li metal (ILC-Li) electrode using nondelaminated 2D Ti 3 C 2 T x MXene stacks (15 μm) coated on a thin Li host (30 μm) was developed. The excellent electrical conductivity and expanded interlayer space of the MXene provide a fast e − /Li + transport while the layer limits the Li growth along the perpendicular direction, thus largely mitigating the dendrite growth. The highly reversible Li deposition/extraction greatly reduces the dead lithium and electrolyte consumption by forming a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…As illustrated in Figure a, although the conductivity of the C‐MXene/AgNW decreased with an increase in the mass ratio of insulating polysiloxane, the C 0.5 ‐MXene/AgNW scaffold still exhibited an high electrical conductivity of 1693 S cm −1 , which facilitated fast charge transportation throughout the scaffold. [ 31,38,46,54 ] When Li was electroplated into the C‐MXene/AgNW scaffold to prepare a Li composite anode (Li@C‐MXene/AgNW), metallic Li was first deposited onto the AgNW network and then uniformly distributed on the cell walls due to the zero nucleation overpotential of Li on silver (Figure 2b; Figure S3, Supporting Information). [ 46,50,55 ] We further confirmed that the Ti 3 C 2 T x MXene surface (with ‐F gourp) is also highly lithiophilic due to its large binding energy density for Li atoms (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure a, although the conductivity of the C‐MXene/AgNW decreased with an increase in the mass ratio of insulating polysiloxane, the C 0.5 ‐MXene/AgNW scaffold still exhibited an high electrical conductivity of 1693 S cm −1 , which facilitated fast charge transportation throughout the scaffold. [ 31,38,46,54 ] When Li was electroplated into the C‐MXene/AgNW scaffold to prepare a Li composite anode (Li@C‐MXene/AgNW), metallic Li was first deposited onto the AgNW network and then uniformly distributed on the cell walls due to the zero nucleation overpotential of Li on silver (Figure 2b; Figure S3, Supporting Information). [ 46,50,55 ] We further confirmed that the Ti 3 C 2 T x MXene surface (with ‐F gourp) is also highly lithiophilic due to its large binding energy density for Li atoms (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 25,26 ] Furthermore, a strongly lithiophilic porous host can lower the Li nucleation overpotential and direct Li nucleation throughout the entire framework to accommodate volume changes during cycling. [ 6,27–29 ] Accordingly, a variety of conductive and/or lithiophilic materials, such as nanostructured silver, [ 27 ] carbonaceous materials, [ 28–30 ] MXenes, [ 31–33 ] and metal oxides, [ 34,35 ] have been developed as efficient 3D porous Li hosts to improve the cycle performance of Li metal composite anodes at high current densities (>5 mh cm −2 ) and areal capacities (>5 mAh cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…After simulating the system in the NPT ensemble for 50 ns whatever the electric field exist or not, what is noteworthy is that that the radial distribution function (RDF) of Li-Al had two peaks which represents DSN may have two Li ion solvation structures. Combining with 7 Li-NMR and 19 F-NMR, they identified the conclusion and reported the Li ion transport mechanism in DSN. First, the pulsatile Li ions are uniting with lower Al centers where the Li-Al distance is 0.32 nm to form Complex 1.…”
Section: Artificial Interfacementioning
confidence: 93%
“…Because of the largely available interspaces in MXene arrays, the growth of lithium was confined in the stripshaped channels (Figure 17h-k). [159b] Besides, other 3D scaffolds for Li metal anodes such as MXene/rGO aerogel (Figure 18a), [160] MXene/graphene framework (Figure 18b), [161] and interlayer-calated thin lithium electrode [162] were also designed for high performance and dendrite-free lithium metal batteries. Notably, Qian et al developed a novel method by using an amorphous liquid metal nucleation seed on MXene films to induce isotropic lithium nucleation and growth, so as to inhibit the growth of lithium dendrite (Figure 18c).…”
Section: Lithium Metal Anodementioning
confidence: 99%